1981
DOI: 10.1159/000123153
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of LHRH Neurons and Their Pathways in the Rat Hypothalamus

Abstract: LHRH neurons and fiber tracts have been studied immunohistochemically in rats. After the intraventricular infusion of colchicine, a number of immunoreactive LHRH neurons were consistently evident in the preoptico-septal area and in the diagonal band of Broca. The immunoreactive fiber tracts originating in those areas were classified into two groups: preoptico-terminal and preoptico-infundibular tracts. The former terminated in the OVLT. The latter was further divided into the mediobasal and laterobasal tracts;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
57
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 22 publications
(34 reference statements)
4
57
0
Order By: Relevance
“…We have recently shown that GABA inhibited spontaneous activity of most of the ARC neurons (NISHIHARA et a1.,1986). Since rat ARC is poor in LHreleasing hormone (LHRH) cell bodies (KAWANO and DAIKOKU, 1981), the inhibitory action of GABA on LH secretion might be mediated by ARC neurons other than LHRH neurons. It has been reported that injection of relatively large doses of GABA…”
mentioning
confidence: 99%
“…We have recently shown that GABA inhibited spontaneous activity of most of the ARC neurons (NISHIHARA et a1.,1986). Since rat ARC is poor in LHreleasing hormone (LHRH) cell bodies (KAWANO and DAIKOKU, 1981), the inhibitory action of GABA on LH secretion might be mediated by ARC neurons other than LHRH neurons. It has been reported that injection of relatively large doses of GABA…”
mentioning
confidence: 99%
“…Since the MPN is located adjacent to the OVLT where the cell bodies and fibers containing LHRH are reported to be concentrated (Setalo et al, 1976 ;Ibata et al, 1979 ;Kawano and Daikoku, 1981 ;Hoffman and Gibbs, 1982 ;King et al, 1982 ;Shivers Endocrinol. Japon.…”
mentioning
confidence: 99%
“…Previous research has alluded to the distribution or projection of the LH-RH neurons in the brain [12,14,43]. Kawano and Daikoku [12] studied the distribution of LH-RH neurons in the diencephalon, and proposed two distinct pathways in the rat brain. One is a mediobasal pathway originating from the preoptic area, which runs straight down the sagittal center of the basal layer of the third ventricle.…”
Section: Discussionmentioning
confidence: 99%